RICH PICTURE ANALYSIS OF THE UNIVERSITY ENTREPRENEURIAL ECOSYSTEM FOR GEN Z - Hendra Halim; Meutia Dwi Novita Sari; Khoirul Amri; Muhammad Zahran Hibatullah (FINANSIA : Jurnal Akuntansi dan Perbankan Syariah, 2026)
This study maps the university-based entrepreneurship education ecosystem for Generation Z in Aceh using SSM and an RP approach. The aim is to uncover actors, flows, bottlenecks, and leverage points that turn learning into entrepreneurial action. Data were collected through document review, short questionnaires, semi-structured interviews, and RP workshops involving students, lecturers, incubator managers, university leaders, industry/SME partners, financiers, and government. The RP synthesis and reflexive thematic analysis identified four system leverage points and highlighted obstacles such as fragmented coordination, limited seed funding, misaligned calendars, and policy/administrative friction. The results show that aligning the curriculum with incubation milestones, codifying readiness rubrics, and applying evidence-based micro-grants strengthen the path from class to customer. This study suggests setting up an Entrepreneurial Ecosystem Council and quarterly RP reviews to coordinate cross-unit decisions and accountability.